Behaviour analysis of H_bridge high_voltage capacitor banks fault on 230_kV substation using discrete wavelet transform - Pathomthat Chiradeja; Praikanok Lertwanitrot; Atthapol Ngaopitakkul; Chaichan Pothisarn (My University, 2023)
Abstract The protection of traditional high‐voltage capacitor banks relies on an unbalance relay which operates when an internal fuse is blown. However, the unbalance relay cannot indicate the cause of the fault. Thus, an operator wastes time and human resources investigating the fault issues. In this paper, a fault which occurred in a 230‐kV power system of Electricity Generating Authority of Thailand was observed by performing simulations using the Power Systems Computer Aided Design (PSCAD) program. The study system based on the double bus station and 72 MVAR capacitor banks was installed in the form of a back‐to‐back topology. Three scenarios were considered: normal condition, fault occurrence in one capacitor bank and fault occurrence in both capacitor banks. Current characteristics such as the current phase and difference in unbalance current were considered. In addition, discrete wavelet transform was applied to solve the ambiguity of current generated from the PSCAD. The authors’ results suggest that identifying fault events using a coefficient of wavelet is more efficient than relying on the current amplitude. The findings mentioned in this paper can be applied in a traditional power system protection scheme to enhance a system's reliability.
Keywords: Fuse (electrical); Power Systems Fault Detection